A simple formula for prediction of plastic collapse pressure of steel ellipsoidal heads under internal pressure. (November 2020) - Zheng, Jinyang; Zhang, Zekun; Li, Keming; Yu, Yehong; Gu, Chaohua
Abstract: Plastic collapse is a critical failure mode considered in the design of ellipsoidal heads under internal pressure. It is significant to develop a formula to calculate plastic collapse pressure of ellipsoidal heads. First, we use a finite element method to calculate plastic collapse pressure, taking into account the effects of strain hardening and geometric strengthening. Second, we investigate the effects of material and geometric parameters on plastic collapse pressure. Based on parametric study, a simple formula is proposed for predicting plastic collapse pressure of ellipsoidal heads. Finally, in order to verify the accuracy of the proposed formula, a series of burst experiments are performed on full-scale ellipsoidal heads which cover various geometric parameters, various material types, and various manufacturing methods. Comparison between the predictions of the proposed formula and the experimental results of 33 full-scale ellipsoidal heads shows that the proposed formula provides a good prediction of plastic collapse pressure of steel ellipsoidal heads under internal pressure. Highlights: Nonlinear FEM is used to calculate plastic collapse pressure of ellipsoidal heads. A simple formula is proposed for predicting plastic collapse pressure. A series of burst experiments are performed to verify accuracy of the formula.